Bevacizumab-induced esophageal pleural fistula during maintenance therapy without radiation in lung cancer - Ting Wang (BMC, 2021)
Abstract Background Esophageal pleural fistula (EPF) is a rare but fatal complication associated with bevacizumab use; however, cases reports of EPF caused by bevacizumab have not been previously published. Case presentation A 66-year-old male patient diagnosed with stage IV lung adenocarcinoma on April 24, 2020 received 6 cycles of platinum-containing dual chemotherapy combined with bevacizumab followed by three cycles of bevacizumab monotherapy. Five days before admission, he experienced chest tightness, dyspnea, and right chest pain. Bed-side X-ray examination revealed a massive right hydrothorax, and food was found in the extracted pleural effusion. EPF was further confirmed by upper gastrointestinal radiography after oral administration of iohexol. The patient underwent jejunostomy as the distal esophagus could not be identified on gastroscopy, and eventually died of septic shock on January 16, 2021. Conclusions It is necessary to pay attention to EPF during bevacizumab use in patients with or without risk factors.